KORELASI FAKTOR SOSIAL EKONOMI RUMAH TANGGA DENGAN TINGKAT PENUNGGAKAN PENGEMBALIAN KREDIT P4K DI KECAMATAN MUARA BANGKAHULU KOTA BENGKULU - Nabiu, Musriyadi; Reflis, Relfis; Aswin, Aswin (Jurnal AGRISEP, 2009)
This research is intended to study characteristics of P4K creditors who are delinquent their credit payments, examine factors influencing their late P4K credit payments.  From 40 P4K creditors, only 23 creditors are able to accessed for this research and willing to participate.  Rank spearman correlation and t-test methods are used to analyze the data gathered from respondents.  The research finds that the level of family income and respondent’ perception on rural development are highly correlated to the level of P4K credit payment while number of family, working motivation and respondents perception on P4K program are not.